Expressing Property Concepts in Ga - Otoo, Y.A. (University of Ghana, 2014)
This study investigated Property concepts in Ga using the Framework-free Grammatical theory (Haspelmath 2008). The study examined three main syntactic categories namely adjectives, verbs and nouns that are used to expressed property concepts in Ga. The morphological, syntactic and semantic properties of these three categories were investigated. Morphologically, most of the adjectives used as property concepts agree with the head noun in number, with the exception of those adjectives whose sources are mainly from nouns and a few that are derived from verbs. Verbs that are employed to express property concepts were mainly stative and may not necessarily agree with the subject but always express a property of whatever noun is found in the subject position. Nouns that precede head nouns to serve as property concepts do not inflect to show number agreement with the head noun but those nouns that occur after the head (nominal adjectives) do agree in number. Syntactically, the attributive role of property concept words is played by all the three categories. Although the predicative role is played by adjectives, they may occur in the same forms or be nominalized, and verbs in predicative positions serve as heads of verb phrases. Six semantic types of Dixon’s adjective classes were identified to be filled by adjectives, and nouns were found to be in the Human Propensity class. The order of multiple property concepts were found not to be strictly ordered, either in attributive or predicative positions.
Thesis (PhD)-University of Ghana, 2014
Keywords: Ga; Syntactic; Semantic Properties; Verbs